A simple approach for branch current computation in load flow analysis of radial distribution systems - Prasad, K.; Sahoo, N. C.; Chaturvedi, A.; Ranjan, R. (MANCHESTER UNIV PRESS, 2007)
The purpose of this paper is to expose students to a simple and efficient load flow algorithm for a radial distribution system (RDS). The basic structure and properties of the RDS are discussed, followed by an illustrative description of the load flow algorithm. The proposed load flow algorithm exploits the tree-type structure of the RDS and uses data structures efficiently. The flowchart and pseudo-codes of the algorithm have been included to help the students in writing their own program. The time and space complexity of the algorithm have also been discussed. The treatment and analysis will be useful for students' understanding of RDS, use of data structures in programming, and approximate complexity analysis of algorithms. The instructors can effectively use the contents of the paper for a basic lecture on RDS (PDF files of the Microsoft PowerPoint slides and C language program code can be downloaded from the website http://www1.mmu.edu.my/similar to nirod/).